Use of Internet technologies in teaching Russian - Aitpayeva, A.S.; Grigoryeva, I.V.; Khairova, G.M. (Ye.A.Buketov Karaganda State University Publishing house, 2015)
Appearance of the Internet and its general distribution plays a great role in teaching languages. In the article modern internet-technologies in educational process are considered. Authors pay special attention to the problems of distance education by means of innovative technologies. Principles of work are described with such technologies in teaching Russian, as podcasting, screen-casting, webinar and others. Authors prove the great significance of internet-education in the modern world, its basic advantages are discussed.
Орыс тілі сабағында интернет-технологияларды қолдану
Использование интернет-технологий в преподавании русского языка
Keywords: Internet technologies; teaching language; distance teaching; podcasting; screencast; webinar; digital native; digital immigrants; multimedia materials